The Effect of Nitrogen and Phosphorus Fertilizer on the Vegetative Growth of Red Chili (Capsicum annuum L.) - Afifatun Nisa; Yeni Ika Pratiwi; Mahrus Ali; Nurlina; Nurul Huda (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
Red chili peppers (Capsicum annuum L.) is a type of vegetable that has economic value high and contains various compounds that are useful for human health. The aim is to determine the extent of the effect of Nitrogen and phosphore on the vegetative growth of red chili plants. This study used a two- factor factorial Randomized Block Design (RAK) method. The first factor is the dose of Nitrogen Fertilizer consisting of three levels, namely N1 (5 gr/plant), N2 (10 gr/plant), and N3 (15 gr/plant), the second factor is the dose of Phosphore fertilizer with two levels, namely P1 (10 gr/plant) and P2 (15 gr/plant). Observation variables include plant height, number of leaves, and number of branches. The results showed that there was a real interaction between nitrogen and phosphore fertilizers. Nitrogen Fertilizer treatment was significantly different from plant height, number of leaves and number of branches. The best Nitrogen Fertilizer treatment was at the N3 dose level (15 gr/plant). Furthermore, in the Phosphore fertilizer treatment, the best results were obtained at the P2 level (15 gr/plant) which affected plant height, number of leaves, and number of branches.